2021
DOI: 10.3390/s21010303
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Olfactory Profile of Rapeseed Oil as a Function of Heating Time and Ratio of Volume and Surface Area of Contact with Oxygen Using an Electronic Nose

Abstract: The process of deep fat frying is the most common technological procedure applied to rapeseed oil. During heat treatment, oil loses its nutritional properties and its original consumer quality is lowered, which is often impossible to determine by organoleptic assessment. Therefore, the aim of the study was to correlate markers of the loss of the nutritional properties by rapeseed oil related to the frying time and the surface area of contact with oxygen with changes in the profile of volatile compounds. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The characterization and discrimination of aroma compounds in the pre-and postrigor roasted mutton could also be successfully identified by GC-O-MS, among which hexanal and 1-octen-3-ol were key odorants and resulted in the difference of aroma profile in samples. The flash GC e-nose performance in the discrimination was consistent with respect to GC-O-MS, which was identical to previous studies [8,28]. These results indicated that hexanal and 1-octen-3-ol might be potential markers for discriminating the pre-and postrigor roasted mutton.…”
Section: Pre-and Postrigor Roasted Mutton Were Discriminated Based On Key Aroma Compounds By Gc-o-ms and Gc E-nosesupporting
confidence: 88%
See 1 more Smart Citation
“…The characterization and discrimination of aroma compounds in the pre-and postrigor roasted mutton could also be successfully identified by GC-O-MS, among which hexanal and 1-octen-3-ol were key odorants and resulted in the difference of aroma profile in samples. The flash GC e-nose performance in the discrimination was consistent with respect to GC-O-MS, which was identical to previous studies [8,28]. These results indicated that hexanal and 1-octen-3-ol might be potential markers for discriminating the pre-and postrigor roasted mutton.…”
Section: Pre-and Postrigor Roasted Mutton Were Discriminated Based On Key Aroma Compounds By Gc-o-ms and Gc E-nosesupporting
confidence: 88%
“…The flash GC e-nose was a combination of GC and e-nose, which could effectively separate compounds and identify differences, such as virgin olive oils [7]. In particular, the integration of e-nose and GC-MS could comprehensively elucidate the aroma difference in samples, such as roasted bread, heated oil and virgin olive oil [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The second group consists of compounds with higher molecular weight than that of parent triacylglycerols, that is, trimers, oligomers of triacylglycerols, and dimmers. The third group of compounds, that is, volatile substances, has a considerable impact on the sensory characteristics and quality of fried food and heated oil (Karami et al, 2020a(Karami et al, , 2020cRusinek et al, 2021). American Oil Chemists' Society (AOCS) has developed various indicators to assess the state of oil oxidation, such as the anisidine index (AnV), the acidity index (AV), the peroxide index (PV), and the Totox index.…”
mentioning
confidence: 99%
“…Technologies based on various types of sensors are now widely used in many fields of both industry and science. The most common types are optical sensors used to determine the content and concentration of gases or liquids [1,2], temperature sensors to measure the course of thermal processes [3,4], humidity sensors to determine the humidity level in studied environments [3,5], electrochemical sensors to detect volatile organic compounds in raw materials and food products [6,7], or force sensors to measure the mechanical properties of raw materials and products of plant origin [4,[8][9][10]. Sensors are increasingly being used in precision agriculture, which has recently been developing very quickly, also with the use of information technologies and other techniques [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, in the study carried out by Marek et al [6], the origin of coffee was distinguished on the basis of PCA analysis of the results of measuring the aromas of roasted coffee. On the other hand, the PCA analysis of results of a study on aromas and mechanical properties of stored bread performed by Rusinek et al [7] allowed correlating the parameters obtained with the onset of bread spoilage due to the formation of mold, which in the initial phase was not yet visible but was detected with the use of an electronic nose and a force sensor for examining the flesh of stored bread. The list of applications is open and there are growing numbers of newer applications of both sensors and statistical methods, the combination of which can provide an explanation and a completely new interpretation of the problem under study.…”
Section: Introductionmentioning
confidence: 99%